The Dynamics of Political Embeddedness in China*. (March 2017) - Haveman, Heather A.; Jia, Nan; Shi, Jing; Wang, Yongxiang
Economic transitions in countries that move from state planning and redistribution to market exchange create business opportunities but also uncertainty, because many interdependent factors—modes of exchange, types of products, and forms of organizations—are in flux. Uncertainty is even greater when the country's political institutions remain authoritarian because the rule of law is weak and state bureaucrats retain power over the economy. This study of listed firms in China, which has recently seen economic transition but persistent authoritarianism, shows that in such contexts, firms can reduce uncertainty by developing relationships with state bureaucrats, which help firms learn how state bureaucracies operate and engender trust between firms and bureaucrats. Together, knowledge and trust stabilize operations and help persuade bureaucrats to lighten regulatory burdens, grant firms access to state-controlled resources, and improve government oversight. Our results show that as economic transitions proceed and uncertainty increases, business–state ties increasingly improve firm performance. We also investigate two likely contingencies, industry and firm size, and two important causal mechanisms, access to bank loans and protection from related-party loans, and show that the value of business–state relations varies over time, depending on the trajectory of both economic and political institutions.